Dampak Pendapatan di Bulan Suci Ramadan dalam Meningkatkan Penjualan (Studi Kasus Pedagang yang berjulanan di Pusat Pasar Medan) - Fadillatunnisa Fadillatunnisa; Zuhrinal M. Nawawi (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine the positive impact for traders in the holy month of Ramadan. The holy month of Ramadan is a month full of blessings and glory, where Muslims compete to get quite a lot of rewards, and there are also many ways that can be done to get rewards in the holy month of Ramadan, one of which is about the economy. So the holy month of Ramadan is one way where people who have small businesses or trades have the opportunity to get materials because the needs needed by the community during the month of Ramadan until Eid are very high and the desire to fulfill all their needs is increasing, so people's interest in shopping Muslims are increasing and the income of small business owners is increasing. The data used in this study are primary data and secondary data. The research method used is a qualitative research method with a descriptive analysis approach. The results showed that sales income during the holy month of Ramadan at the Medan market center experienced a considerable increase due to the increasing needs of consumers who wanted to provide food, drinks, clothing and the need for supplies to welcome or celebrate Eid al-Fitr with their families and relatives. -Respectively, so the needs of consumers in the month of Ramadan until Eid al-Fitr are increasing so that sales income is also increasing.